HUBUNGAN ANTARA PEMBELAJARAN PENJAS DENGAN PERILAKU SOSIAL SISWA DI SMAN 4 KOTA KUPANG - Simson Robinson Kerihi; Michael Johannes H. Louk (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
ABSTRACT This research is motivated by the social behavior of students who are both individuals and groups still have not been able to adjust to their environment in physical education learning (Physical Education). The purpose of this study was to determine social behavior in physical education learning and obtain an overview of the relationship between physical education learning and social behavior of students. The research method used is a descriptive research method in class X students at SMAN 4 Kupang, amounting to 300 students, and for the sample taken 20% of the population that is 60 students. The instrument used was a questionnaire or questionnaire and researchdocumentation. Before knowing the results of the research the questionnaire was tested first, the statement items were made as many as 50, then after being tested the questionnaire there were invalid statements so that the valid statements were 47 items. The results of this study obtained the amount of 10,120 with an average of 168.07 and a standard deviation of 15.04 then for the normality test obtained Lo 0.48 with normal conclusions because Lo <Lt. Significant test results for the correlation coefficient for this study obtained r 0.86 with a very strong correlation interpretation, while tcount 12.8> ttable 2.00. Then the description of these results shows a significant relationship between physical education learning and social behavior of students.Keywords: Physical Education Learning, Student Social Behavior